Circuit analysis 1 [ with MATLAB computing and Simulink/SimPowerSystems modeling - Karris, Steven T.; Karris, Steven T.
An introductory text on electric circuit analysis with real-world examples and problem supplemented with MATLAB computations, and Simulink/SimPower models